The coactivator role of histone deacetylase 3 in IL-1-signaling involves deacetylation of p65 NF-kappaB - Ziesché, Elisabeth; Kettner-Buhrow, Daniela; Weber, Axel; Wittwer, Tobias; Jurida, Liane; Soelch, Johanna; Müller, Helmut; Newel, Doris; Kronich, Petra; Schneider, Heike; Dittrich-Breiholz, Oliver; Bhaskara, Srividya; et al. (My University, 2012)
Histone deacetylase (HDAC) 3, as a cofactor in co-repressor complexes containing silencing mediator for retinoid or thyroid-hormone receptors (SMRT) and nuclear receptor co-repressor (N-CoR), has been shown to repress gene transcription in a variety of contexts. Here, we reveal a novel role for HDAC3 as a positive regulator of IL-1-induced gene expression. Various experimental approaches involving RNAi-mediated knockdown, conditional gene deletion or small molecule inhibitors indicate a positive role of HDAC3 for transcription of the majority of IL-1-induced human or murine genes. This effect was independent from the gene regulatory effects mediated by the broad-spectrum HDAC inhibitor trichostatin A (TSA) and thus suggests IL-1-specific functions for HDAC3. The stimulatory function of HDAC3 for inflammatory gene expression involves a mechanism that uses binding to NF-?B p65 and its deacetylation at various lysines. NF-?B p65-deficient cells stably reconstituted to express acetylation mimicking forms of p65 (p65 K/Q) had largely lost their potential to stimulate IL-1-triggered gene expression, implying that the co-activating property of HDAC3 involves the removal of inhibitory NF-?B p65 acetylations at K122, 123, 314 and 315. These data describe a novel function for HDAC3 as a co-activator in inflammatory signaling pathways and help to explain the anti-inflammatory effects frequently observed for HDAC inhibitors in (pre)clinical use.
Keywords: histone deacetylase 3 (HDAC3); NF-kappaB p65; positive gen-regulation of IL-1; co-activator in inflammatory signaling pathways; ddc:610